2000
DOI: 10.1046/j.1464-410x.2000.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CD44 isoform v10 expression and its prognostic value in renal cell carcinoma

Abstract: Objective To examine the expression of CD44 isoform v10 (CD44v10) in patients with renal cell carcinoma (RCC), analyse its role in RCC and its relationship with conventional clinical-histopathological experience. Materials and methods Sixty-four RCC specimens and ®ve metastatic specimens were analysed immunohistochemically using a CD44v10 speci®c antibody. Thus the aims of the present study were to examine the correlation between the immunohistochemical expression of CD44v10 protein with conventional histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Two studies focused on CD44v5 expression, and only one study concluded that the CD44v5 non-expression group has a higher mortality rate than the expression group 24 25 . One study with CD44v10 demonstrated that high CD44v10 expression correlates with high tumour grade, clinical stage and short survival 26 . The expression of CD44v3 was not detected in one study 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies focused on CD44v5 expression, and only one study concluded that the CD44v5 non-expression group has a higher mortality rate than the expression group 24 25 . One study with CD44v10 demonstrated that high CD44v10 expression correlates with high tumour grade, clinical stage and short survival 26 . The expression of CD44v3 was not detected in one study 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, CD44v3 positive rate is also very low in one study 22 . Another study reported that CD44v10 expression significantly correlates with histological grade, clinical and pathological stages and cancer-specific survival 26 . Two studies obtained significantly different results on the expression rates (91.7% and 6.4%) of CD44v5 24 25 .…”
Section: Discussionmentioning
confidence: 99%
“…CD44 v6 overexpression has been correlated with advanced tumor stage and poor survival in non‐Hodgkin's lymphoma and colon cancer 20. CD44 v10 correlation with renal cell carcinoma histologic grade, staging, and poor prognosis has been reported 37…”
Section: Discussionmentioning
confidence: 98%
“…CD44 v10‐containing isoforms have been studied regarding tumor progression in breast and renal cell carcinoma 23, 37. Although all CD44 isoforms share HA binding domains, certain CD44 variant isoforms, such as CD44 v10, exhibit significantly reduced affinity for HA binding 27.…”
Section: Discussionmentioning
confidence: 99%
“…Although a contradictory result has been reported concerning the prognostic significance of CD44 immunoexpression in RCC [23], most other studies have shown that high CD44 expression in RCC is associated with poor survival [7,13,17], a significant risk of progression [5,16], and poor tumor differentiation [23]. CD44 expression was shown to be correlated with tumor grade, with higher immunoreactivity observed in higher grade tumors [2,7,23].…”
Section: Discussionmentioning
confidence: 99%